Smart and Sustainable Cities and Buildings. - (:unkn) unknown (Springer, 2020)
This book brings together the papers presented at the Smart and Sustainable Built Environments Conference, 2018 (SASBE). This latest research falls into two tracks: smart and sustainable design and planning cities; and the technicalities of smart and sustainable buildings. The growth of smart cities is evident, but not always linked to sustainability. This book gives an overview of the latest academic developments in increasing the smartness and sustainability of our cities and buildings. Aspects such as inclusivity, smart cities, place and space, the resilient city, urbanity and urban ecology are prominently featured in the design and planning part of the book; while energy, educational buildings, comfort, building design, construction and performance form the sub-themes of the technical part of the book.
Keywords: Nachhaltige Stadtentwicklung; Smart City; Smart Building; Green Building; Resilienz; Inklusion; Stadtökologie; Urbanität; Öffentlicher Raum; Freiraumnutzung; Energieeinsparung; Hitzebelastung; Klimaanpassung; Schutzmaßnahme; Belichtung; Stadtgrün; Nachhaltiges Bauen; Kreislaufwirtschaft; Internationaler Vergleich; Grüne Infrastruktur